THE VIABLE APPLICATION OF THE IMMEDIATE PROCESS FOR THE EFFECTIVE PROCESSING OF COMPUTER FRAUD CRIMES AND PROPOSALS TO CHILDREN AND ADOLESCENTS FOR SEXUAL PURPOSES THROUGH TECHNOLOGICAL MEANS IN THE JUSTICE SYSTEM - Meneses Ochoa, Jean Paul (2023)
This research work is based on the problems related to the increase in the number of registered complaints of computer crimes, which negatively affects the perception of citizen insecurity and the procedural overload in the justice system, there being a need on the part of the State to address this problem. In response to this, considering that data have been collected that demonstrate that the Immediate Process has obtained effective results in the justice system, the objective of this research work is to expose the viable application of the Immediate Process as an effective tool for the processing of the crimes of Computer Fraud and Proposals to children and adolescents for sexual purposes through technological means regulated by Law No. 30096 – Computer Crime Law. For this, the crime figures, procedural overload of the justice system, citizen insecurity and the growth of complaints for computer crimes are observed in order to show the problem to be addressed. Then an analysis of the Immediate Process is carried out, in addition, the results obtained in its application in the justice system are observed. Subsequently, an analysis of the crimes of Computer Fraud and Proposals to children and adolescents for sexual purposes through technological means is carried out. Finally, through an analysis of cases related to the aforementioned computer crimes, it is posible to expose the viability of the Immediate Process for the effective prosecution of these computer crimes.